Peran Minat Pembelian Konsumen sebagai Mediasi Kualitas Produkterhadap Keputusan Pembelian pada Perusahaan Kue - Ari Adriansyah, Muhammad; Aryanto, Rudy; Toindo, Harly; Agusthina, Shirley (Binus Business Review, 2013)
Cookie companies are demanded to improve their product quality, product quality is one of the important things. Because with a good product quality, it will deliver purchase intention; with the intention earned by customer, it will also deliver the purchase decision process. The purpose of this research is to analyse the effect of product quality towards purchase intention and its impact on the purchase decision process. The method used in this research is descriptive-associative, with Path Analysis. Questionnaires were distributed to J&C Cookiesâ consumers. The findings of this research show that the product quality gives a big influence to customerâs purchase intention and gives a big and positive impact on purchase decision process of J&C Cookiesâ customers.